Historical and archaeological data on the region of Taza and its surroundings in ancient periods. - bakkai, lakhder; Bouyhiaoui, Ezzédine (Journal of Social Sciences and Humanities, 2021)
The archaeological research aims to highlight the facts of the field of important scientific nature and help find mechanisms to allow researchers, in various Scientific fields, access the peculiarities of the archeological findings extracted from the ground on the basis that everything that comes out of the underground is a new source of knowledge. The requirements of this work field result in many problems dealing with inventory, study and maintenance of archaeological material, which confirms the importance reorienting the archaeological research policy in Algeria, especially since some of the landmarks or sites that are damaged or prominent are now in danger. So Our motive on an archaeological site or an entire archaeological area means that we defend the archaeological unity or cultural communication or what is also known in the historical sequence, we have in the Taza area of Prince Abdelkader Tower in the Wilayat of Tissemsilt a worthy field of study that diagnoses these problems. It highlights the historical importance of the region through its historical sites from which we will show here what dates back to the old periods, and suffice to point out here that the archaeological sites to be presented did not appear in the Atlas of Stefan Gsell on one hand and never mentioned in the Romanian defense system The "touch", and even its physical evidence is still unknown.